KEBIJAKAN DIVIDEN DAN BI RATE SEBAGAI PEMODERASI LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP NILAI PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2011-2017 - Ananto Dwi Antoro; Sri Hermuningsih (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
The purpose of this study is dividend payout ratio and BI Rate as moderation of liquidity, profitability, and leverage on financial firm value in Indonesia Stock Exchange within period 2011-2017. Research using purposive sampling method for taking sample, as many as 10 banks based on criteria. The research used secondary data from company’s annual report. The data were analyzed by using SPSS and SmastPls 3.2.7. The result showed that :1) the Liquidity and BI Rate have negative effect on company’s value but the effect were not significant, 2) profitability has a positive significant effect on firm value. 3) Leverage has a positive effect on firm value but the effect was not significant. 4) Dividend have a positive significant effect on company’s value. 5) Liquidity, profitability and leverage moderated by dividend dan BI Rate has no significant effect on firm value. Key words : Company’s value, Liquidity, Profitability, Leverage, Dividend.